Dinamika Transmigrasi di Desa Makmur Jaya: Sejarah, Perkembangan, dan Dampaknya - Rozi, Fahrul; Daulay, Maraimbang; Nasution, Kasron (Medan Resource Center, 2025)
This study explores the dynamics of transmigration in Makmur Jaya Village, focusing on its historical development and impact on community life. It examines three aspects: (1) the initial settlement process, (2) socio-economic development, and (3) socio-religious changes among transmigrants. Using a qualitative historical-sociological approach, data were collected through heuristics, source criticism, interpretation, and historiography. The findings indicate that transmigration began in 1981, leading to the establishment of Mukti Jaya and later expanding into Makmur Jaya Village. Economically, livelihoods diversified from agriculture to trade, civil service, and services. Socio-culturally, the community preserved Javanese traditions, such as ketoprak performances. Religiously, transmigrants contributed to Islamic development through mosque construction, religious education, and community celebrations. This study concludes that transmigration in Makmur Jaya Village successfully improved community welfare while maintaining cultural and religious values.